Analysis Of The Design Of An Information System For Lecturer Performance Evaluation - siti hartinah; Moeng Sakmar; Rizky Andhika Surya (Universitas Ibn Khaldun Bogor, 2025)
Faculty Performance Evaluation (FPE) is a crucial process in ensuring academic quality and human resource development in higher education institutions. However, the traditional FPE monitoring process often faces obstacles such as time inefficiency, lack of transparency, and difficulties in real-time data recapitulation. This study aims to design an information system model capable of monitoring all stages of the EKD process in a structured, centralized, and automated manner. The method used in this design is Object-Oriented Methodology with the help of UML (Unified Modeling Language) modeling, such as Use Case Diagram, Activity Diagram, and Class Diagram, to visualize the system architecture. The main result of this research is an information system blueprint model that includes modules for monitoring evaluation status, reporting progress, and automatic notification features to relevant parties (lecturers, students, and management). This system design is expected to improve the accountability and efficiency of the EKD process, provide accurate monitoring data, and support management in making decisions related to the quality and performance development of lecturers at the institution.